The Influence of Capital Structure and Management Quality on Firm Value With Capital Expenditure as Moderating Variable in the Primary Consumer Goods Sector on the Indonesia Stock Exchange - Andre Prasetya Willim (PT Mattawang Mediatama Solution, 2022)
The purpose of this study is to determine the effect of capital structure and management quality on firm value and the effect of capital expenditure as a moderating variable on the effect of capital structure and management quality on firm value. The population in this study is the Primary Consumer Goods Sector Companies on the Indonesia Stock Exchange (IDX) from 2016 to 2020, of which there are 92 companies. The sampling technique is purposive sampling, so the research sample is 59 companies. The analysis stages of this study include descriptive statistical analysis, classical assumption testing, multiple linear analysis, correlation coefficient analysis and determination, hypothesis testing, and moderating regression analysis. The results of the study show that capital structure and management quality have a positive effect on firm value, and capital expenditure has a moderating effect that weakens the effect of capital structure on firm value, while capital expenditure has a moderating effect that strengthens the influence of management quality on firm value.